2018
DOI: 10.1002/mbo3.666
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of new Muscodor endophytes from gramineous plants in Xishuangbanna, China

Abstract: The endophytic fungi Muscodor spp. produce volatile organic compounds (VOCs) which can inhibit and even kill pathogenic fungi, bacteria, and nematodes. Nine endophytic fungal strains, isolated from the shoots of gramineous plants including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Earlier, naphthalene and sabinene monohydrates were reported by Daisy et al (2002) and Singh et al (2011) from Muscodor vitigenus and Phomopsis sp., respectively. The endophytic VOCs are majorly found to be bio-active, and our experimental outcomes support the same (Banerjee et al, 2010a,b;Kudalkar et al, 2012;Mao et al, 2019;Pena et al, 2019).…”
Section: Volatile Organic Compound-mediated Anti-fungal Actionsupporting
confidence: 89%
“…Earlier, naphthalene and sabinene monohydrates were reported by Daisy et al (2002) and Singh et al (2011) from Muscodor vitigenus and Phomopsis sp., respectively. The endophytic VOCs are majorly found to be bio-active, and our experimental outcomes support the same (Banerjee et al, 2010a,b;Kudalkar et al, 2012;Mao et al, 2019;Pena et al, 2019).…”
Section: Volatile Organic Compound-mediated Anti-fungal Actionsupporting
confidence: 89%
“…However, the isolation method was mainly considered the ability of the isolated strains to produce diffusible antifungal compounds. Recent studies have demonstrated that VOCs as well as the diffusible antifungal compounds produced by PGPR have equally important functions in antifungal activities (Mao, Chen, & Xia, ; Ossowicki, Jafra, & Garbeva, ; Xie, Zang, & Wu, ). In this study, the dual‐culture and double‐plate chamber method were introduced to distinguish the ability of the isolated strains to produce diffusible and volatile antifungal compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological characteristics of Induratia species were based on colony and mycelial characteristics, as reproductive structures have never been observed in any culture medium (Strobel et al 2001;Zhang et al 2010;Chen et al 2019;Mao et al 2018). However, Samarakoon et al (2020) found the sexual state of two specimens from Thailand, I. ziziphi and I. thailandica.…”
Section: Discussionmentioning
confidence: 99%